PELESTARIAN TRADISI HINDU BALI DI BANJAR KARANG DESA KECAMATAN TANJUNG KABUPATEN LOMBOK UTARA - Ida Bagus Benny Surya Adi Pramana (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The national economic equity program through the rate of use of technology promoted by the local government can run well, so it is necessary for a young generation to be willing to help develop pasraman for the advancement of Hindus, especially in Banjar Karang, Tanjung Village, Tanjung District, North Lombok Regency. The community of Dusun Karang Desa, Pemenang Barat Village, North Lombok Regency is the majority of the population 40% self-employed & 20% civil servants. The number of people is approximately 345 people consisting of 115 heads of families, but who are active in Banjar Karang Desa are approximately 65 heads of families. Given the lack of pasraman management, it is important for institutions to carry out community service. Through community service, it is hoped that it can help the Karang Desa Community, Pesikian Karang Mumbul, works of dharma laksana and Pesikian Karang Mumbul, Karya Dharma Laksana and Pesikian Karang Lebah to get to know Hindu customs and culture need to be considered through learning in the field. The implementation phase lasts for a period of 18–22 July 2022. The material provided is an effort to enrich people's knowledge about Balinese dance, dharma gita, Balinese script, Yoga, Pencak Silat, Religious Counseling and games. The children and youth agreed to understand the importance of preserving culture as the identity of a nation. implementation, this community service activity can help residents increase their knowledge.